Gender component in the content of school textbooks on ukrainian literature as the basis for the development of egalitarian consciousness of the individual (Pedagogy of Higher and Secondary Education, 2013)
Basyuk L. В. Gender component in the content of school textbooks on ukrainian literature as the basis for the development of egalitarian consciousness of the individualIn the article the textbook on Ukrainian literature for the seven grade of Middle School of General Education was decomposed in the context of state reform regarding the gender constituent of educational realm. The question of gender-balanced content of the educational materials, in particular the textbooks, was actualized and the peculiarities of gender orientation were examined. Considering that literature being an important part of identity formation, the impact of its content on the development of egalitarian consciousness of the individual was emphasized.
Keywords: school textbook; egalitarian consciousness; the gender component of the content of education